Ibrutinib for patients with rituximab-refractory Waldenström's macroglobulinaemia (iNNOVATE): an open-label substudy of an international, multicentre, phase 3 trial. Issue 2 (February 2017) - Dimopoulos, Meletios A; Trotman, Judith; Tedeschi, Alessandra; Matous, Jeffrey V; Macdonald, David; Tam, Constantine; Tournilhac, Olivier; Ma, Shuo; Oriol, Albert; Heffner, Leonard T; Shustik, Chaim; García-Sanz, Ramón; et al.
Summary: Background: In the era of widespread rituximab use for Waldenström's macroglobulinaemia, new treatment options for patients with rituximab-refractory disease are an important clinical need. Ibrutinib has induced durable responses in previously treated patients with Waldenström's macroglobulinaemia. We assessed the efficacy and safety of ibrutinib in a population with rituximab-refractory disease. Methods: This multicentre, open-label substudy was done at 19 sites in seven countries in adults aged 18 years and older with confirmed Waldenström's macroglobulinaemia, refractory to rituximab and requiring treatment. Disease refractory to the last rituximab-containing therapy was defined as either relapse less than 12 months since last dose of rituximab or failure to achieve at least a minor response. Key exclusion criteria included: CNS involvement, a stroke or intracranial haemorrhage less than 12 months before enrolment, clinically significant cardiovascular disease, hepatitis B or hepatitis C viral infection, and a known bleeding disorder. Patients received oral ibrutinib 420 mg once daily until progression or unacceptable toxicity. The substudy was not prospectively powered for statistical comparisons, and as such, all the analyses are descriptive in nature. This study objectives were the proportion of patients with an overall response, progression-free survival, overall survival, haematological improvement measured by haemoglobin, time to next treatment, and patient-reported outcomes according to the Functional Assessment of Cancer Therapy-Anemia (FACT-An) and the Euro Qol 5 Dimension Questionnaire (EQ-5D-5L). All analyses were per protocol. The study is registered atClinicalTrials.gov, numberNCT02165397, and follow-up is ongoing but enrolment is complete. Findings: Between Aug 18, 2014, and Feb 18, 2015, 31 patients were enrolled. Median age was 67 years (IQR 58–74); 13 (42%) of 31 patients had high-risk disease per the International Prognostic Scoring System Waldenström Macroglobulinaemia, median number of previous therapies was four (IQR 2–6), and all were rituximab-refractory. At a median follow-up of 18·1 months (IQR 17·5–18·9), the proportion of patients with an overall response was 28 [90%] of 31 (22 [71%] of patients had a major response), the estimated 18 month progression-free survival rate was 86% (95% CI 66–94), and the estimated 18 month overall survival rate was 97% (95% CI 79–100). Baseline median haemoglobin of 10·3 g/dL (IQR 9·3–11·7) increased to 11·4 g/dL (10·9–12·4) after 4 weeks of ibrutinib treatment and reached 12·7 g/dL (11·8–13·4) at week 49. A clinically meaningful improvement from baseline in FACT-An score, anaemia subscale score, and the EQ-5D-5L were reported at all post-baseline visits. Time to next treatment will be presented at a later date. Common grade 3 or worse adverse events included neutropenia in four patients (13%), hypertension in three patients (10%), and anaemia, thrombocytopenia, and diarrhoea in two patients each (6%). Serious adverse events occurred in ten patients (32%) and were most often infections. Five (16%) patients discontinued ibrutinib: three due to progression and two due to adverse events, while the remaining 26 [84%] of patients are continuing ibrutinib at the time of this report. Interpretation: The sustained responses and median progression-free survival time, combined with a manageable toxicity profile observed with single-agent ibrutinib indicate that this chemotherapy-free approach is a potential new treatment choice for patients who had heavily pretreated, rituximab-refractory Waldenström's macroglobulinaemia. Funding: Pharmacyclics LLC, an AbbVie Company.